Educational Experiences of the Mising Tribe Learners of Majuli An Exploratory Study - Phukan, Moni Monjuri; Chander, Subhash (INDIAN EDUCATIONAL REVIEW, 2025)
The Mising Tribe, an Indo-Mongoloid group in Assam, dominates the socio-cultural landscape of Majuli island. The educational status of the Mising Tribe was discouraging, compared with the rest of the population. This research study aimed to explore the educational experiences of learners from the Mising community and the factors influencing their experiences. The study used a qualitative paradigm. The participants from the Mising community of fifth, sixth, seventh and eighth standards from Assamese vernacular-medium government secondary schools were selected through incidental sampling. The sampled teachers were interviewed with the highest density of Mising Learners from the Uttar Kamalabari cluster and Madhya Majuli Cluster to gather data for the research. The parents who gave their consent were also interviewed. The findings revealed that the learners from the Mising community in Majuli face significant barriers to education due to flooding disruptions, lack of mother tongue instruction, inadequate school infrastructure and socio-economic hardships. Limited awareness of government schemes, gender biases and low parental support further hindered their consistent attendance and academic progress.